2018
DOI: 10.1016/j.maturitas.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in Mediterranean breast cancer patients compared with those in healthy women

Abstract: Severely reduced 25(OH)D levels were detected in patients with breast cancer, particularly after recent chemotherapy. These 25(OH)D levels had partially recovered over the long term, but still remained much lower than in the healthy population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In comparison with the control group, we found more patients with VD deficiency (56.1% vs. 37.2%) among the BC patients. Decreased levels of VD in BC patients compared to control subjects were observed previously [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], and our results confirm these findings with the LC–MS/MS methodology. Presented findings could be a result of decreased sun exposure.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison with the control group, we found more patients with VD deficiency (56.1% vs. 37.2%) among the BC patients. Decreased levels of VD in BC patients compared to control subjects were observed previously [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], and our results confirm these findings with the LC–MS/MS methodology. Presented findings could be a result of decreased sun exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Vitamin D is known to play an important role in musculoskeletal tissues in addition to bone 14 , including muscle 15 , cartilage 16 , and synovium 17 . Previous studies carried out in women with ER+ early breast cancer receiving AI treatment, who also frequently present vitamin D deficiency 18 , provide evidence of the possible effects of vitamin D status on musculoskeletal health 9,19 . In our cohort study, the main musculoskeletal effect of vitamin D supplementation was found in AI-related arthralgia, consistent with a previous study by Prieto-Alhambra et al in 2011 11 .…”
Section: Discussionmentioning
confidence: 99%